Selectivity filters and cysteine-rich extracellular loops in voltage-gated sodium, calcium, and NALCN channels - Stephens, Robert F.; Guan, W.; Zhorov, Boris S.; Spafford, J. David (Frontiers in Physiology, 2015)
How nature discriminates sodium from calcium ions in eukaryotic channels has been difficult to resolve because they contain four homologous, but markedly different repeat domains. We glean clues from analyzing the changing pore region in sodium, calcium and NALCN channels, from single-cell eukaryotes to mammals. Alternative splicing in invertebrate homologs provides insights into different structural features underlying calcium and sodium selectivity. NALCN generates alternative ion selectivity with splicing that changes the high field strength (HFS) site at the narrowest level of the hourglass shaped pore where the selectivity filter is located. Alternative splicing creates NALCN isoforms, in which the HFS site has a ring of glutamates contributed by all four repeat domains (EEEE), or three glutamates and a lysine residue in the third (EEKE) or second (EKEE) position. Alternative splicing provides sodium and/or calcium selectivity in T-type channels with extracellular loops between S5 and P-helices (S5P) of different lengths that contain three or five cysteines. All eukaryotic channels have a set of eight core cysteines in extracellular regions, but the T-type channels have an infusion of 4–12 extra cysteines in extracellular regions. The pattern of conservation suggests a possible pairing of long loops in Domains I and III, which are bridged with core cysteines in NALCN, Cav, and Nav channels, and pairing of shorter loops in Domains II and IV in T-type channel through disulfide bonds involving T-type specific cysteines. Extracellular turrets of increasing lengths in potassium channels (Kir2.2, hERG, and K2P1) contribute to a changing landscape above the pore selectivity filter that can limit drug access and serve as an ion pre-filter before ions reach the pore selectivity filter below. Pairing of extended loops likely contributes to the large extracellular appendage as seen in single particle electron cryo-microscopy images of the eel Nav1 channel.